I-JAR: a mobile application to learn Jawi using mobile Augmented Reality (mAR) framework / Nor Farahin Mohd Johari … [et al.] - Mohd Johari, Nor Farahin; Ishak, Norshahidatul Hasana; Zaini, Hazrati; Mazlan, Nurul Asma; Khairul Nizam, Nadiatul Mardiana (Akademi Pengajian Bahasa, 2021)
Jawi is the Arabic letters that play an important role in spreading Islam and cultural administration in Malaysia. In the 13th century until the 20th century, Jawi writing was used as the main writing system in the form of Malay language. The usage of Jawi was faded and no longer exists as the official writing in Malaysia after the invasions of western colonial power in which Jawi scripts are changed to Rumi. Learning Jawi through traditional form such as textbook can be hard for children to visualize the characters. There is also possibility that the learning method unable to attract them to learn Jawi. Augmented reality (AR) is an emerging form of experience that make use the combination of text, audio, video, image, and animation. The use of these elements in Augmented Reality are utilized to support the teaching and learning process. This study developed I-JAR: Interactive Jawi Augmented Reality by adapting mobile Augmented Reality (mAR) framework for children from age 4 to 12 years old to learn Jawi. The evaluation scale adapted is based on usability testing which consists of five elements: Ease of Operation, Ease of Learning and Memory, Usage Convenience, Satisfaction, and Individuation. The total results of each elements are 0.88, 0.93, 1.00, 0.88, and 0.87, respectively. The study indicates that the usage of AR is a good approach for students in learning Jawi.